TGF-β1 promotes cerebral cortex radial glia-astrocyte differentiation in vivo - Stipursky, Joice; Francis, Daniel; Dezonne, Rômulo Sperduto; Bérgamo de Araújo, Ana Paula; Souza, Lays; Moraes, Carolina A.; Alcantara Gomes, Flávia Carvalho (Frontiers in Cellular Neuroscience, 2014)
The major neural stem cell population in the developing cerebral cortex is composed of the radial glial cells, which generate glial cells and neurons. The mechanisms that modulate the maintenance of the radial glia stem cell phenotype, or its differentiation, are not yet completely understood. We previously demonstrated that the transforming growth factor-β1 (TGF-β1) promotes radial glia differentiation into astrocytes in vitro (Glia 2007; 55:1023-33) through activation of multiple canonical and non-canonical signaling pathways (Dev Neurosci 2012; 34:68-81). However, it remains unknown if TGF-β1 acts in radial glia-astrocyte differentiation in vivo. Here, we addressed the astrogliogenesis induced by TGF-β1 by using the intraventricular in utero injection in vivo approach. We show that injection of TGF-β1 in the lateral ventricles of E14,5 mice embryos resulted in radial glia fibers disorganization and premature gliogenesis, evidenced by appearance of GFAP positive cells in the cortical wall. These events were followed by decreased numbers of neurons in the cortical plate. Together, we also described that TGF-β1 actions are region-dependent, once radial glia cells from dorsal region of the cerebral cortex demonstrated to be more responsive to this cytokine compared with radial glia from lateral cortex either in vitro as well as in vivo. Our work demonstrated that TGF-β1 is a critical cytokine that regulates radial glia fate decision and differentiation into astrocytes in vitro and in vivo. We also suggest that radial glia cells are heterogeneous population that acts as distinct targets of TGF-β1 during cerebral cortex development.